MANAGEMENT MODEL FOR REDUCING ACCIDENTS FROM ROAD FREIGHT - อุตเจริญ, ยุทธจักร์ (Journal of Buddhist Anthropology, 2021)
The Objectives of this research article were to the confirmatory factor analysis (CFA) of the management model for reducing accidents from road freight, together with examining the consistency of the model. The sample comprised of 300 supervisors who responsible for transportation management. This study used quantitative method and analysis. The instrument used for data collection data was a questionnaire. The data was analyzed with both descriptive and inferential statistics. The descriptive statistics included percentage, mean, and standard deviation. On the other hand, the inferential statistics comprised of first order CFA and second order CFA for examining the consistency of the model and the empirical data The results showed that the vehicle management is the most important factor for reducing accidents from road freight, in overall. The main latent variables for management model for reducing accidents from road freight ranking from the highest factor loading score were Traffic environment, Vehicle, and Driver, respectively. The observe variable with highest factor loading score was the selection of vehicle to suit the job The validation of a goodness of fitted model yielded a Chi-square of 1.188, GFI = 0.988, AGFI = 0.971, TLI = 0.985, NFI = 0.953, RMSEA = 0.025, and RMR = 0.013. Therefore, it can be concluded that the factors of the management model for reducing accidents from road freight were consistent with the empirical data